Vertical distribution and pollution assessment of TN, TP, and TOC in the sediment cores of cage farming areas in Dongshan Bay of southeast China - Zhen-Zhen, Cai; Jian, Zeng; Miao-Feng, Yang; Yong-Qing, Lin; Hui-Dong, Zheng; Dong-Lian, Luo; Shuang-Cheng, Jiang; Tuan-Yu, Guo; Sheng-Hua, Zheng (Frontiers in Environmental Science, 2023)
Cage farming is an important means of aquacultural production, while its potential environmental pollution needs to be further investigated. In this study, Dongshan Bay was taken as an example to investigate whether long-term cage farming in a semi-closed bay would cause environmental pollution via vertical distribution assessment. The four sediment cores (YB1, YB2, B1, and B2) were collected from two cage farming areas. Total nitrogen (TN), total organic carbon (TOC), and total phosphorus (TP) were measured. The results showed a negative correlation between TN and TOC and the sediment depth at four sampling sites, and TP was also negatively correlated with the depth at three sites. The average TN (1,405.8, 1,413.8, 1,115.7, and 936.1 mgkg−1) and TP (1,206, 1,141.6, 1,064.6, and 932.8 mgkg−1) values of the four sites were markedly higher than the safety level, with the indexes STN, STP, FF, and ON of the four sites indicating moderate to severe pollution of nitrogen and phosphorus. Particularly, the YB1 and YB2 sites in the area with lower current speed have more severe pollution. The C/N ratio uncovered that the organic matter (OM) might mainly derived from the phytoplankton and nonfibrous plants as a result of excessive fish feed and feces. Collectively, the results indicated that long-term (more than 10 years) cage farming activity in a semi-closed bay such as Dongshan Bay had a negative impact on the environmental quality. Despite limitations in sample size and the absence of stable isotopic analyses, this study enhances our understanding of environmental changes and endogenous pollution risks in shallow marine aquaculture areas. Moreover, it suggests practical approaches such as implementing alternative farming and fallowing periods, should be conducted to mitigate the pollution.